2019
DOI: 10.1007/jhep08(2019)022
|View full text |Cite
|
Sign up to set email alerts
|

Weak gravity conjecture, black hole entropy, and modular invariance

Abstract: In recent literature, it has been argued that a mild form of the Weak Gravity Conjecture (WGC) is satisfied by wide classes of effective field theories in which higher-derivative corrections can be shown to shift the charge-to-mass ratios of extremal black holes to larger values. However, this mild form does not directly constrain low-energy physics because the black holes satisfying the WGC have masses above the cutoff of the effective theory. In this note, we point out that in string theory modular invarianc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 62 publications
(114 reference statements)
1
38
0
Order By: Relevance
“…Being supersymmetric and, hence, extremal, the mass of the black hole coincides with the sum (up to moduli factors) of the four charges associated to the constituents. This computation reveals that the charge-to-mass ratio of these configurations is not modified by higher-curvature corrections, a behaviour that has been argued to occur in nonsupersymmetric extremal black holes [37][38][39].…”
Section: Four-charge Black Holementioning
confidence: 58%
“…Being supersymmetric and, hence, extremal, the mass of the black hole coincides with the sum (up to moduli factors) of the four charges associated to the constituents. This computation reveals that the charge-to-mass ratio of these configurations is not modified by higher-curvature corrections, a behaviour that has been argued to occur in nonsupersymmetric extremal black holes [37][38][39].…”
Section: Four-charge Black Holementioning
confidence: 58%
“…Hence, it has little predictive power about low energy effective theories in itself. It has been recently suggested that it might be possible to relate the mild and strong versions of the WGC using modular invariance of string theory [15]. Given the growing amount of evidence in favor of the mild WGC, this seems a promising idea and it would be interesting to test it for a regular extremal black hole system of string theory.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the latter possibility corresponds to a milder version of the conjecture that would just provide information about states far heavier than the Planck mass, and hence it is less useful for the swampland program. Of course, the two scenarios are not mutually exclusive, and it is conceivable that they might be related [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [38,39,54], another SLð2; ZÞ symmetry, i.e., the modular symmetry of the 2D CFT of the worldsheet (or the holographic dual) was used to upgrade the WGC to stronger forms. See Sec.…”
Section: Introductionmentioning
confidence: 99%